Characterization of Philippine rice - a case of mixed rice variety - Macadaan, Cindy R.; Azanza, Maria Patricia V. (2023)
This study presented variabilities in physico-chemical and microbial qualities of raw and
resulting ready-to-eat (RTE) cooked rice prepared by a cook-chill processing system utilizing
commercially available Philippine rice, marketed under the trade name Super Angelica.
Significant variations (p < 0.05) in raw rice physical qualities were established based on the
results of the grading and classification evaluation system described by the Philippine National Standards–Bureau of Agriculture and Fisheries Standards PNS/BAFS 290:2019 and amylose content. Likewise, variations in trends of texture cooked rice qualities were established in the resulting microwaved reheated chilled RTE rice stored up to 7 d in terms of hardness, cohesiveness, and adhesiveness. The pH values and microbial quality of reheated cooked rice were significantly affected by processing and storage conditions. The study recommended the strict implementation of the National Food Authority (NFA) Circular OCS-2018-J-0 that limits the classification of local commercial rice into four categories – namely, regular, well-milled, premium, and special – as an official replacement to the current use of market trade or fancy names for rice supplies. Likewise, the study cited the need for drafting a national regulation that will eventually reflect the actual cultivar names of rice being marketed in the country to avoid the rumbling of commercial rice.
Keywords: Rice -- Variety; Rice -- Quality; Cooking (Rice)